The Effect of Different Bonding Agent Curing Times on Microleakage of Composite Restorations in Enamel and Dentin Margins Using Two Curing Systems - Mansoreh Mirzaei; Reza Nejatbakhsh; Esmaeil Yassini; Hamid Kermanshah; ladan Ranjbar Omrani (Islamic Dental Association of Iran, 2013)
Background and Aim : Lack of appropriate seal is one of the major problems in composite restorations. Properties of the bonding system can play a crucial role in sealing ability of these restorations. The aim of this study was to evaluate the microleakage of composite restorations with varying irradiation time for curing dentin bonding agents with two different curing devices in class V cavities .   Materials and Methods : In this experimental study, 60 intact extracted human molars and premolars were subjected to standard class V cavity preparations. Cavities were divided to six groups. Following etching, Excite bonding agent was applied and light cured using QTH and LED systems for 20, 30 and 40 seconds and cavities were filled with composite. The filled cavities were subjected to 3000 thermal cycles with 5-55 ° C temperatures. Teeth were immersed into 0.5% basic fushin dye and sectioned occlusogingivally from the restoration middle area and the microleakage was determined using stereomicroscope by a 5-scaled rankings. Data were analyzed by Mann-Whitney and Kruskal-Wallis tests with p<.0.05 as the level of significance .   Results : No leakage was found in enamel margins. The type of light curing device did not have any significant effect on dentin margins microleakage (p>0.05). Furthermore, no significant reduction in microleakage scores were observed in the restorations irradiated with different curing times (p>0.05 ).    Conclusion : QTH and LED curing units in 20, 30, and 40 s curing time did not have any significant effect on microleakage of class V composite restoration margins .